Natural resource dependence and war nexus: new insights - Al Shami, Farah (2025)
This paper examines the channels through which resource dependence affects the probability of war. We consider all types of war within a worldwide panel dataset of all countries and territories, spanning the period 1960-2022. We systematically estimate the probability of war using a set of economic and geographic characteristics, including democracy, demography, legal origin, militarism, and sectoral composition. Using a panel probit model, we find that natural resources rents, military expenditures, and the presence of a common law tradition significantly increase the probability of war occurrence. However, we notice that this probability is decreasing in the level of economic development and democratization, and with the size of the services sector and trade openness. We also find that the effect of resource dependence varies by level of economic development, continent, landlocked status, legal origin, colonial history, and war type with civil wars being the salient type. Overall, we provide novel and updated evidence on an important dimension of the vexing question of the so-called ‘resource curse’.